Exploring Bacterial Colonies in Solid Foods or Model Foods Using Non-Destructive Techniques - Anne Thierry (Frontiers Research Topics, 2016)
Bacteria are always present in foods, either as initial contamination or as technological agents. In solid foods, they are immobilized and develop as colonies. So far, there is a lack of knowledge about the bacteria in colonies, growth and physiology. Non-destructive and resolute techniques, such as fluorescent microscopy, now allow investigating the world of bacteria in colonies and their surroundings in food, at the microscopic scale.